Data Markets in Making: The Role of Technology Giants - Heli Koski; Mika Pantzar (The Research Institute of the Finnish Economy (ETLA), 2019)
This paper focuses on the role of large technology companies' entry and expansion to the data-intensive market areas via their technological development and strategic acquisitions of companies. We analyze the evolvement of personal data related innovation in various data-intensive domains. We find that the ideas related to personal data are increasingly protected by patents. The growth in the numbers of personal data related patents was relatively modest from 2005 to the early 2010s, but it has intensified since 2011. Large technology companies' entry to various new market areas is reflected in an exponential increase in patent applications particularly in the artificial intelligence domain. Furthermore, we find that the number of artificial intelligence/data analytics companies acquired by the data giants has escalated during the 2010s. Patent and acquisition data further echo technology giants' intentions to expand their activities into the financial and personal health services. Overall, the data show the data giants' buyouts are frequently targeted to companies active in the markets outside their core business. Our analysis illustrates how the divergencies in the data giants' innovation activities and strategic acquisitions have led them to each conquer their specific areas of dominance in the global markets for data.
Keywords: G34; L12; L25; O33; 330; Data economy; Innovation; Patents; Acquisitions; Technology giants